Poly(5-tert-butyl)benzothiophene: a soluble form of polyisothianaphthene with a large nonlinear optical response - BLAU, WERNER; DRURY, ANNA (My University, 1998)
A soluble form of polybenzothiophene has been produced and chemically characterised. NMR spectroscopy indicates that there is a large quinoidal character contribution to the ground state of the polymer. The third order nonlinear optical properties of the polymer have been probed and it is found that the response is relatively large in the near-infrared region
PUBLISHED
Keywords: nonlinear optical properties; nonlinear optical properties